Umbilical Cord Blood Bilirubin as a Predictor of Significant Hyperbilirubinemia Requiring Phototherapy among Full-term Healthy Neonates: A Prospective Study - Preethi B Patil; Prasanna Saka; Abhay K Chidananda (Indian Journal of Medical Biochemistry)
Aim and background: Jaundice is a clinical condition characterized by transient bilirubin conjugation deficiency resulting in neonatal hyperbilirubinemia. Hyperbilirubinemia is defined as a serum total bilirubin concentration greater than 95th centile for the hour of life. Approximately 60% of term and 80% of preterm infants are affected with hyperbilirubinemia, which may lead to complications such as brain neuron damage after several years. Early discharge of healthy-term newborns after delivery has become a common practice, which may be the cause for readmission during the early neonatal period. Universal follow-up within 1–2 days of early discharge, pre-discharge serum total bilirubin, transcutaneous bilirubin measurement, and universal clinical assessment of risk factors of developing jaundice are various strategies to predict significant neonatal hyperbilirubinemia. An association between cord blood bilirubin levels and subsequent risk of neonatal hyperbilirubinemia has been reported. However, the utility of cord blood bilirubin as a screening test to predict subsequent hyperbilirubinemia has been widely debated. We aimed to verify whether cord blood bilirubin at birth could be used as a predictor of significant neonatal hyperbilirubinemia requiring phototherapy among full-term neonates. Materials and methods: Cord blood bilirubin was estimated in 110 neonates immediately after delivery. These neonates were followed up for the next 3 days and serum total bilirubin was estimated on the third day of life. Neonates with significant hyperbilirubinemia requiring phototherapy were designated as cases and those without hyperbilirubinemia as controls. The association between cord blood bilirubin and serum total bilirubin was determined followed by the identification of the cut-off level of cord blood bilirubin that could predict significant neonatal hyperbilirubinemia requiring phototherapy among term neonates. Results: Among 100 neonates followed up, 50 developed significant hyperbilirubinemia requiring phototherapy. The mean ± SD of cord blood bilirubin was 2.66 ± 0.65 and serum total bilirubin estimated on day 3 of life was 16.16 ± 1.6 and the difference was statistically highly significant at a p-value of <0.00 with paired t-test. The cord blood bilirubin and day 3 serum bilirubin were positively correlated with an r-value of 0.087. The specificity and sensitivity with cord blood bilirubin of 2.5 mg/dL were 98 and 56%, and with day 3 bilirubin of 11.5 mg/dL was 72 and 100%, respectively. Conclusion: A cut-off of 2.5 mg/dL in cord blood bilirubin can be used to predict significant neonatal hyperbilirubinemia requiring phototherapy among full-term neonates. Clinical significance: Umbilical cord blood bilirubin measurement is a simple, economical, and non-invasive method to predict subsequent neonatal hyperbilirubinemia which can aid clinicians in early discharge of normal neonates and selective follow-up of high-risk infants.